Gen Z Growth Strategy for Rohlik.cz in E-Commerce - Knorr, David; Stříteský, Václav; Bobrytskyy, Serhiy; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
This thesis aims to formulate an actionable and research-based growth strategy for Rohlik.cz to better attract and retain Gen Z consumers. The theoretical part establishes a framework connecting e-commerce, e-grocery, and Gen Z consumer behavior, addressing a gap in both academic and industry knowledge. The research follows a case study design, combining a literature-based analysis with qualitative methods. The practical part is based on 30 semi-structured interviews with Gen Z consumers and 3 expert interviews to enrich the strategic perspective. Findings reveal that while Rohlik.cz is perceived as offering high-quality products and services, many Gen Z respondents are not fully aware of the extent of this value. Promotion, persuasion, and personalization emerged as key strategic levers to bridge this perception gap. The resulting strategy is structured using the 7Ps framework and includes influencer collaborations, referral program, and AI-powered personalization features. A phased implementation plan (2025–2030) and a financial model support the strategy’s feasibility, with a realistic annual net contribution of 480 million CZK. Beyond its business relevance, the thesis contributes to the underexplored intersection of Gen Z and online grocery, offering insights applicable to broader e-commerce strategies.
Vedoucí práce: Václav Stříteský
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses